Simultaneously Cooperative, but Serially Antagonistic: A Neuropsychological Study of Diagonistic Dyspraxia in a Case of Marchiafava-Bignami Disease - Kazumi Hirayama; Kaori Tachibana; Nobuhito Abe; Hideaki Manabe; Takahisa Fuse; Tetsuro Tsukamoto (Behavioural Neurology)
We describe a patient with Marchiafava-Bignami disease who showed, in addition to signs of callosal interruption, a peculiar form of diagonistic dyspraxia. Unlike the typical diagonistic dyspraxia, both of the patient’s hands could simultaneously cooperate in a sequence of bimanual actions. More specifically, his right hand could start a commanded action with the cooperation of his left hand. However, once the action was completed, his left hand started an antagonistic action, undoing the result, with the cooperation of his right hand. Once this countermanding action was completed, the original action started again. These antagonistic actions repeated themselves alternately unless he was restrained. The patient's diagonistic dyspraxia was apparent in only some bimanual actions, and he showed no diagonistic dyspraxia when performing voluntary actions; the antagonistic actions occurred in response to oral commands or by imitation. Magnetic resonance imaging showed symmetrical demyelination with partial necrosis in the genu, body, and anterior splenium of the corpus callosum. We speculate that the bimanual coordination is possible because part of the corpus callosum is intact, whereas the antagonistic actions may be caused by conflict between the two hemispheres due to interhemispheric disinhibition elicited by the demyelinated part of the corpus callosum.